Pengaruh Media Pembelajaran Jeopardy Game terhadap Aktivitas dan Hasil Belajar Peserta Didik - Nuraini Nuraini; Misykat Malik Ibrahim; Jamilah Jamilah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
The Jeopardy Game is a learning media designed to assess students' ability to identify and remember factual information. This study aimed to describe students' learning activities and outcomes, whether or not they used Jeopardy Game learning media. Another aim was to define the impact of the media on the activities and students' learning outcomes. This was a quasi-experimental study with a non-equivalent control group design. The data analysis techniques were descriptive statistical analysis and inferential statistics. The sample in this study was 20 students from class VIII A, selected as the experimental class, and class VIII C, as the control class. The instrument used is a learning outcome test on respiratory system material. The results showed that students taught using the Jeopardy Game learning media had an average learning outcome of 72.82 and learning activities of 70.85. Meanwhile, students taught using conventional learning models have an average learning outcome of 58.35 and a mean value of learning activities 45.6. The results of inferential statistical analysis obtained a significant value for activity and learning outcomes of 0.000. This value indicates that the sign < = 0.00 < 0.05 so that H0 is rejected and H1 is accepted. It appears that the Jeopardy Game learning media influenced students' activities and learning outcomes in PondokPesantren Al-Wahid PancaLautang's respiratory system material for class VIII Sidenreng Rappang District.